The effects of perceived usefulness, confirmation and satisfaction on continuance intention in using massive open online course (MOOC) - Aisha Aminu Daneji; Ahmad Fauzi Mohd Ayub; Mas Nida Md. Khambari (Knowledge Management & E-Learning: An International Journal, 2019)
Massive Open Online Course (MOOC) has been playing an important role in the latest e-learning initiative and has obtained a widespread popularity in many universities. However, the low course completion rates of students have become an outstanding issue that should not be neglected. Based on the Expectation-Confirmation Model (ECM), this study examines the effects of students’ perceived usefulness, confirmation and satisfaction on MOOC continuance intention. Structural Equation Modeling (SEM) was used to validate the proposed model and hypotheses. Participants were 368 undergraduate students enrolled in a MOOC platform. The study’s result revealed that confirmation has significant effects on students’ perceived usefulness and satisfaction. Perceived usefulness and satisfaction have significant effects on students’ continuance intention while perceived usefulness has no significant effects on students’ satisfaction. This study will help to outspread our understanding of what influence students to continue using MOOC.